622 Tranexamic Acid Use in Meningioma Surgery – a Systematic Review and Meta-Analysis. (19th August 2022) - Gillespie, CS; Clynch, A; Richardson, GE; Mustafa, M A; Islim, AI; Kumar, S; Keshwara, SM; Millward, CP; Jenkinson, MD
Abstract: Aim: Meningioma surgery is associated with increased intraoperative bleeding and transfusion requirement. Tranexamic Acid (TXA) has been used in medical and surgical practice to reduce haemorrhage. This review aimed to evaluate the effect of TXA use on bleeding and transfusion requirement, and functional outcomes in meningioma surgery. Method: A systematic review and meta-analysis was conducted in accordance with the PRISMA statement and registered in PROSPERO (CRD42021292157). Six databases were searched up to November 2021. Random effects meta-analysis was performed to delineate blood loss, transfusion requirements, postoperative complications, operation time, and hospital stay. Results: Four studies (181 patients) were included (three randomised control trials, one clinical trial). TXA use significantly reduced Intraoperative blood loss (mean difference 315.69mls [95% CI -532.94 to -98.54]) and transfusion requirement (OR 0.52 [95% CI 0.27–0.98]). Factors not affected by TXA use were operation time (mean difference 0.09 hours [95% CI -0.11 to 0.29]), Post-operative seizures (OR 0.87 [95% CI 0.31–2.49]), hospital stay (mean difference -2.4 days [95% CI -3.18 to -1.62]), and disability after surgery (OR 0.47 [95% CI 0.14–1.61]). Risk of bias was low (n=3) or unclear (n=1) in all included studies. Heterogeneity was high in length of operation (I 2 = 90%), and hospital stay outcomes (I 2 = 92%), and low in all others. Conclusions: TXA use reduces blood loss and transfusion requirement in meningioma surgery, but not post-operative complications, or disability after surgery. Larger trials are required to investigate the impact of TXA on patient-focussed post-operative outcomes.